A Prophetic Medicine: Potential Therapeutic Effect of Nigella sativa for Osteoarthritis - Al Hajiri, Aufar Zimamuz Zaman; Abdillah, Diaz Syafrie; Zulfikar, Mohammad Qoimam Bilqisthi (UNUSA Press, 2020)
Osteoarthritis (OA) is the most common type of arthritis (inflammation of the joints). OA can affect all cartilage throughout the body, including the spine, but mainly attacks the legs from the pelvis, especially the knee to the ankle which affects about 10% of men and 18% of women over 60 years old. Pharmacotherapy, surgery, and complementary therapy are the currently managements of OA. Nigella sativa (NS) is one of the herbal plants which is part of the prophet's medicines in the Islamic world which still used. Thymoquinone (TQ) is one of NS compound, has an anti-inflammatory effect by inhibit the formation of eicosanoids in leukocytes and lipid peroxidation, or inhibit the expression of PF NF-κB subunits and p50 subunits with TNF-a promoters, and reduce levels of C-reactive protein (CRP). TQ also has a chondroprotective effects mechanism by decreases prostaglandin E2 (PGE) mediated by IL-1β and inhibits MMP synthesis in chondrocytes. Through its anti-inflammatory and chondroprotective effect, NS is a potential therapeutic agent which beneficial use for OA management without toxicological effects when given.